PENINGKATAN PENGETAHUAN DAN SIKAP IBU TENTANG MP-ASI (MAKANAN PENDAMPING AIR SUSU IBU) DI DESA HENDROSARI MENGANTI GRESIK - Yuanita Syaiful; Lilis Fatmawati; Siti Aminah (LP2M Universitas Hasanuddin, 2020)
Increased Knowledge and Attitude of Mothers about Complementary Food for Mother's Milk in Hendrosari Village, Menganti GresikAbstract. ASI complementary foods (MP-ASI) are foods or drinks that contain nutrients, given to infants and children to meet their nutritional needs. MP-ASI is given together with ASI from the age of 6 months to 24 months. As the baby gets older, after the baby is 6 months old, it starts to be introduced with complementary foods to meet its nutritional needs. Too early to give MP-ASI will cause the fulfillment of the baby's milk needs is reduced. MP-ASI less than 6 months of age can increase the risk of diarrhea, dehydration, decreased milk production and allergies. Providing education in the form of health education about the provision of MP-ASI for infants aged 0-6 months is an educational strategy for mothers to apply the knowledge they have acquired and change the wrong attitude independently. The purpose of this activity is to increase knowledge and attitudes about MP-ASI for mothers in the village of Hendrosari Menganti Gresik. The activity was carried out in full involvement of the mother in accordance with the target, starting from educational activities namely health counseling about MP-ASI to mothers who gave MP-ASI to infants younger than 6 months, demonstrating the preparation of MP-ASI with correct consistency and small group discussions. The results of this activity showed an increase in knowledge and attitudes towards mothers about MP-ASI with established indicators of success.Keywords: Health education, knowledge, attitude, MP-ASI.Abstrak. Makanan pendamping ASI (MP-ASI) adalah makanan atau minuman yang mengandung gizi, diberikan pada bayi dan anak untuk memenuhi kebutuhan gizinya. MP-ASI diberikan bersamaan dengan ASI mulai usia 6 bulan hingga 24 bulan. Seiring bertambahnya usia bayi, setelah bayi berusia 6 bulan, mulai diperkenalkan dengan makanan pendamping untuk memenuhi kebutuhan gizinya. Terlalu dini memberikan MP-ASI akan menyebabkan pemenuhan kebutuhan ASI bayi berkurang. MP-ASI kurang dari usia 6 bulan dapat menimbulakn risiko diare, dehidrasi, produksi ASI menurun dan alergi. Pemberian edukasi dalam bentuk pendidikan kesehatan tentang pemberian MP-ASI pada bayi usia 0-6 bulan merupakan strategi pendidikan kepada para ibu untuk mengaplikasikan pengetahuan yang telah didapat dan merubah sikap yang salah secara mandiri. Tujuan kegiatan ini adalah meningkatkan pengetahuan dan sikap tentang MP-ASI pada ibu di Desa Hendrosari Menganti Gresik. Kegiatan dilaksanakan dengan melibatkan secara penuh ibu sesuai sasaran, mulai dari kegiatan edukasi yakni penyuluhan kesehatan tentang MP-ASI pada ibu yang memberikan MP-ASI pada bayi usia kurang dari 6 bulan, peragaan penyiapan MP-ASI dengan konsistensi yang benar dan small group discussion. Hasil kegiatan menunjukkan terjadi peningkatan pengetahuan dan sikap pada ibu tentang MP-ASI dengan indikator keberhasilan yang ditetapkan.Kata kunci : Pendidikan kesehatan, pengetahuan, sikap, MP-ASI.